OBSAFER: Hydrogen Power Plant from Soybean Straw and Tofu Liquid Waste in Kediri District - Nugroho, Aldi; Septianus, Yohanes Maruli Arga; Faizin, Miladia; Firdaus, Muhammad Dimmas; Rafi Afwa, Ahmad Rifaldi; Bahetha, Amelia; Muthmainnah, Salsabila Aminatun (IPTEK The Journal of Engineering, 2024)
Industrial developments result in higher consumption of electrical energy with considerable emissions. Efforts to develop alternative energy are carried out to overcome climate change. Hydrogen, as a clean energy, can be produced from biomass, such as soybean straw waste. The OBSAFER innovation was created to optimize the use of soybean straw and tofu liquid waste in electrical power. The process began with soybean straw waste pre-treated with NaOH and entered into a bioreactor for a dark fermentation process with Clostridium butyricum to produce hydrogen, methane, and carbon dioxide. Then, the gas is separated by a CH4 filter and a CO2 filter, so the main product is hydrogen. The OBSAFER technology can produce 821,751 kWh/year from 21.6 tons of soybean straw waste and Clostridium butyricum from tofu liquid waste.